Online P2P lending industry: an international analysis - Lan, Meijing (2019)
This thesis comprises three essays that explore a number of research questions in the online peer-to-peer (P2P) lending industry from an international perspective. The first essay highlights an intriguing phenomenon in the Chinese online P2P lending market, whereby investors keep lending in platforms when the majority of them fail. This essay shows that investors are able to leverage nonstandard information, especially social capital information, in screening platforms and making investment decisions. Using a hand-collected sample of 6,190 Chinese platforms from June 2007 to June 2017, this essay provides robust evidence that social capital plays a significant role in platform survival inference and its economic significance is stronger than standard information such as financial capital. The findings highlight the contribution of social capital in reducing information asymmetry for investors, and offer policy and practical implications for regulators and risk managers in this innovative and fast-growing industry.